Review of the Grass Feeding Leafhopper Genus Balclutha Kirkaldy (Hemiptera: Cicadellidae: Deltocephalinae) in China - Lu, Lin; Zhang, Yalin; Webb, M. D. (Zootaxa, 2013)
The present paper treats 27 species and one species complex of the leafhopper genus Balclutha Kirkaldy from China, in-cluding descriptions of four new species, Balclutha bidentifurcata, B. parapunctata, B. paralucida and B. tricornis spp. nov., and gives six new records for China. One new synonymy, B. fuscomaculatus Dai, Li & Chen, 2004, as a junior syn-onym of B. saltuella (Kirschbaum, 1868), is proposed. A key to males of Chinese Balclutha species, together with a check-list and figures for the species is provided.